Galectin-9 as a prognostic biomarker in small cell lung cancer - Xu, Yaolin; Guan, Chao; Zhang, Xiaoye (Translational Cancer Research, 2018)
Background: Galectin-9 has been reported to play an important role in the immunoregulation, survival, and growth of different cancers. Our study aims to uncover the clinical significance of galectin-9 in small cell lung cancer (SCLC) postoperatively. Methods: We studied 48 patients with SCLC who underwent surgery from 2008 to 2014. Galectin-9 expression was assessed by immunohistochemistry on tissue and plot survival curves by the Kaplan-Meier curve. Prognostic analysis was conducted via integrating all of the independent indicators into a multivariate Cox analysis for overall survival (OS). Furthermore, we evaluate whether SCLC patients with high or low galectin-9 expression might benefit from chemotherapy or radiotherapy. Results: High galectin-9 expression was significantly correlated with high levels of neuron specific enolase (NSE) expression (P=0.04). We found that galectin-9 (P